Endometrial microbiota in women with and without adenomyosis: A pilot study - Lin, Qi; Duan, Hua; Wang, Sha; Guo, Zhengchen; Wang, Sirui; Chang, Yanan; Chen, Chao; Shen, Minghong; Shou, Hejun; Zhou, Chang (Frontiers in Microbiology, 2023)
The endometrial microbiota plays an essential role in the health of the female reproductive system. However, the interactions between the microbes in the endometrium and their effects on adenomyosis remains obscure. Here, we profile endometrial samples from 38 women with or without adenomyosis to characterize the composition of the microbial community and its potential function in adenomyosis using 5R 16S rRNA gene sequencing. The microbiota profiles of patients with adenomyosis were different from the control group without adenomyosis. Furthermore, analysis identified Lactobacillus zeae, Burkholderia epacian, Weissella confuse, Prevotella copri and Citrobacter freundii as potential biomarkers for adenomyosis. In addition, Citrobacter freundii, Prevotella copri and Burkholderia cepacian had the most significant diagnostic value for adenomyosis. PICRUSt results identified 30 differentially regulated pathways between the two groups of patients. In particular, we found that protein export, glycolysis/gluconeogenesis, alanine, aspartate, and glutamate metabolism were upregulated in adenomyosis. Our results clarify the relationship between the endometrial microbiota and adenomyosis. The endometrial microbiota of adenomyosis exhibits a unique structure and Citrobacter freundii, Prevotella copri and Burkholderia epacian were identified as potential pathogenic microorganisms associated with adenomyosis. Our findings suggest that changes in the endometrial microbiota of patients with adenomyosis are of potential value for determining the occurrence, progression, early diagnosis and treatment of adenomyosis.